The Kite Fighters - Park, Linda Sue.; Park, Eung Won (Clarion Books, 2000)
In Korea in 1473, eleven-year-old Young-sup overcomes his rivalry with his older brother Kee-sup, who as the first-born son receives special treatment from their father, and combines his kite-flying skill with Kee-sup's kite-making skill in an attempt to win the New Year kite-fighting competition.
Keywords: Fiction; Fiction; Contests; Birth order; Fiction; Brothers; Fiction; Kites; Korea; Fiction